EVALUASI PROGRAM PEMBANGUNAN DAN REHABILITASI SARANA DAN PRASARANA TRANSPORTASI YANG BERORIENTASI PADA PEMBANGUNAN KAWASAN PARIWISATA - Anwar, Mufti Nadirsyah Putra; Marsoyo, Agam (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
The development of rural areas is an effort intended to accelerate village development. To achieve this acceleration, a rural area development program (RPKP) was designed, providing a platform to be used in achieving the goals of village and rural area development. The rural area development plan is a program implemented in the Ponelo Kepulauan Rural Area, focusing on marine tourism development through five physically oriented activities. The method used to identify activities is qualitative analysis, with conclusions drawn based on the cumulative percentage values of output classification results. The evaluation used is summative, with a retrospective results evaluation approach. This study found that out of the five activities observed in the program, only one was classified as Relevant, and none were effective in its implementation. Thus, the low percentage of Relevance (20%) and Effectiveness (0%) in the program leads to the conclusion that the development and rehabilitation program for transportation infrastructure oriented towards tourism area development is considered Unsuccessful.